Two new species of Cameraria Chapman (Lepidoptera: Gracillariidae) associated with Salix or Cornus in Japan - Sawada, Masayasu; Yoshizawa, Kazunori; Ohshima, Issei (Zootaxa, 2024)
Two new species of the genus Cameraria Chapman, 1902, Cameraria riparia sp. nov. and Cameraria corni sp. nov., are described from Japan. Larval setal maps, illustrations and/or photographs of wing patterns, wing venations and genitalia are provided for both species, and the systematic positions of the two species are discussed based on their morphologies. The larvae of C. riparia feed on Salix spp. and make blotch mines, whereas C. corni larvae feed on Cornus kousa subsp. kousa and make linear blotch mines. C. riparia was collected on Hokkaido and Honshu Islands, and considerable differences in the male genital characters were detected between the two populations. However, a molecular phylogenetic analysis based on the COI barcode region indicated that there was no clear genetic differentiation between the two populations (maximum divergence, 1.41%). C. corni was collected on Honshu and Kyushu Islands, and this is the first record of the trophic association of Lithocolletinae with Cornaceae.